Quality of life in children with chronic kidney disease - Ari Fibrianto; Hertanti Indah Lestari; Yudianita Kesuma; Moretta Damayanti; Eka Intan Fitriana; Rismarini Rismarini (Indonesian Pediatric Society Publishing House, 2023)
Background Chronic kidney disease (CKD) has become a global burden on the healthcare system and significantly impacts the quality of life of children with the condition. Objective To assess quality of life in children with CKD as well as its relationship with sociodemographic, medical, and psychosocial factors. Methods This cross-sectional analytic study was conducted from June to November 2021 at Dr. Moh Hoesin Hospital, Palembang. Children with CKD aged 2-18 years were included by consecutive sampling. Parents and patients were asked to complete the PedsQL™ generic score scale version 4.0 questionnaire. Results We assessed quality of life in 112 children with CKD from parents' and children's reports in the PedsQL™ questionnaire. Physical and emotional parameters had the lowest scores. Based on parental reports, quality of life was significantly associated with disease severity (P=0.002), behavioral disorders (P=0.007), and sleep disturbances (P=0.001). Based on the children's reports, the factors significantly associated with quality of life were anemia (P=0.044), sleep disturbances (P=0.024), and behavioral disorders (P=0.002). Almost one-third of children with CKD had general impairment of quality of life, both from parental reports (32.1%) and children's reports (33.0%). Conclusion Disease severity, anemia, sleep disturbance, and behavioral disorders were all associated with poorer quality of life in children with CKD.